Вы находитесь на странице: 1из 6

# james (jaj4329) – HW 11.

05 – rusin – (52435) 1
This print-out should have 10 questions. To see that this series is convergent, set
Multiple-choice questions may continue on
the next column or page – find all choices 1
bn = √ .

## 001 10.0 points Then

Which one of the following series is conver- (i) bn+1 ≤ bn , (ii) lim bn = 0 .
gent? n→∞

## ∞ Consequently, by the Alternating Series Test,

X (−1)n−1
1. √ correct the series
2+ n ∞
n=1 X (−1)n−1
∞ √
X 6 2+ n
2. √ n=1
3+ n
n=1
is convergent.

X 3
3. (−1)2n √
002 10.0 points
6+ n
n=1
∞ √ Determine if the series
n−1 2 + n
X
4. (−1) √ ∞
3+ n X 5  nπ 
n=1 cos
n+1 4
Explanation: n=0
Since
∞ ∞
converges or diverges.
X 3 X 3 Similar series are fundamental to the math-
(−1)2n √ = √ ,
6+ n 6+ n ematical description of all musical sounds!
n=1 n=1
use of the Limit Comparison and p-series 1. series diverges
Tests with p = 1/2 shows that this series
is divergent. 2. series converges correct
The same use of the Limit Comparison and
p-series Tests with p = 1/2 shows that the Explanation:
π 
series The basic idea is that cos x is a peri-

X 6 4
√ odic function taking values between −1 and
3+ n
n=1 1. This will enable us to write the given series
also is divergent. as a sum of alternating series. Indeed,
On the other hand, by the Divergence Test,
π1
the series
√ cos(0) = 1, cos = √ ,
∞ 4 2
n−1 2 + n
X
(−1) √
3+ n π   
3π 1
n=1 cos = 0, cos = −√ ,
2 4 2
is divergent because

n−1 2 + n while
lim (−1) √ 6= 0 .
n→∞ 3+ n  
5π 1
This leaves only the series cos(π) = −1, cos = −√ ,
4 2

X (−1)n−1 

 


1
√ . cos = 0, cos = √ ,
2+ n 2 4 2
n=1
james (jaj4329) – HW 11.05 – rusin – (52435) 2
π
and so on for higher multiples of . Thus the
4 3. (0, ∞)
given series can be written as
 1 1 1 1 1 4. (−∞, 0)
5 1+ √ − √ − − √ + √
2 2 4 2 5 6 2 8 2
5. [0, ∞)
1 1 1 1 
+ − √ − √ − −... ,
9 10 2 12 2 13 Explanation:
The given series can be written in the form
which in turn can be written as the sum of
three alternating series ∞ p ∞
n−1 (ln(n))
X X
(−1) = (−1)n−1 f (n)

1 1
 3n
n=2 n=1
5 1− + −...
5 9
with f defined by
 
5 1 1 1
+√ √ − √ + √ −... (ln(x))p
2 2 2 6 2 10 2 f (x) = .
  3x
5 1 1 1 We apply the Alternating Series test. By the
−√ √ − √ + √ −... ,.
2 4 2 8 2 12 2 Quotient Rule,
As each of the series (ln(x))p−1(p − ln(x))
f ′ (x) = < 0
1 1 1 3x2
1− + − +...
5 9 13 when ln(x) > p. Thus f is eventually decreas-
1 1 1 ing for every p, so
− + −...
2 6 10
f (n) > f (n + 1)
1 1 1
− + −... .
4 8 12 for all large n. On the other hand,
But by the Alternating Series Test, each (ln(x))p
lim f (x) = lim = 0.
of these three series is convergent. Conse- x→∞ x→∞ 3x
quently, the given series is
Consequently the series

convergent . X (ln(n))p
(−1)n−1
3n
n=2
003 10.0 points converges for all p in the interval
Determine all values of p for which the series

(−∞, ∞) .
p
n−1 (ln(n))
X
(−1)
3n
n=2
004 10.0 points
terval notation. Determine whether the series

X 3
1. (−∞, ∞) correct √ cos(nπ)
n=0
n+4

## 2. p = {0} converges or diverges.

james (jaj4329) – HW 11.05 – rusin – (52435) 3
Explanation:
1. series converges correct Since
∞ ∞
X
3 3 X 3
2. series diverges (−1) √ = − √ ,
5+ n 5+ n
n=1 n=1
Explanation:
Since cos(nπ) = (−1)n , the given series can use of the Limit Comparison and p-series
1
be rewritten as the alternating series Tests with p = shows that this series is
2

X 3 X∞ divergent. Similarly, since
(−1)n √ = (−1)n f (n)
n=0
n+4 n=0

X 3

X 3
2n
(−1) √ = √ ,
5+ n 5+ n
with n=1 n=1
3
f (x) = √ . the same argument shows that this series as
x+4
well as
Now X∞
5

3 3 3+ n
f (n) = √ > √ = f (n + 1) n=1
n+4 n+5
is divergent.
for all n, while On the other hand, by the Divergence Test,
the series
3 √
lim f (n) = lim √ = 0. ∞
n→∞ n→∞ n+4 n−1 4 + n
X
(−1) √
3+ n
Consequently, by the Alternating Series Test, n=1

## the given series is divergent because

converges . n−1 4 + n
lim (−1) √ 6= 0 .
n→∞ 3+ n
005 10.0 points This leaves only the series

Which one of the following series is conver- X (−1)n−1
gent? √ .
4+ n
n=1

X 5 To see that this series is convergent, set
1. √
3+ n
n=1
1
∞ bn = √ .
X 3 4+ n
2. (−1)2n √
5+ n
n=1 Then
∞ √
n−1 4 + n (i) bn+1 ≤ bn , (ii) lim bn = 0 .
X
3. (−1) √ n→∞
3+ n
n=1
∞ Consequently, by the Alternating Series Test,
X (−1)n−1 the series
4. √ correct
4+ n ∞
(−1)n−1
n=1
X

∞ 4+ n
X 3 n=1
5. (−1)3 √
5+ n is convergent.
n=1
james (jaj4329) – HW 11.05 – rusin – (52435) 4

## 006 10.0 points 007 10.0 points

Determine whether the series Determine whether the series

X cos2 (k) 8 9 10 11 12
(−1)k−1 − + − + −...
2k 12 13 14 15 16
k=1

## is absolutely convergent, conditionally con- is absolutely convergent, conditionally con-

vergent or divergent vergent or divergent.

## 3. divergent 3. absolutely convergent

Explanation: Explanation:
To check for absolute convergence we have In summation notation,
to decide if the series ∞
8 9 10 11 12 X

cos2 (k) − + − + −... = an ,
12 13 14 15 16
X
n=8
2k
k=1
with an given by
is convergent. For this we can use the Com-
parison Test with n
an = (−1)n .
n+4
cos2 (k) 1
ak = , bk = . However,
2k 2k
For then n
lim = 1,
n→∞ n+4
0 ≤ a k ≤ bk ,
so that as n → ∞, an oscillates between val-
since 0 ≤ cos2 (k) ≤ 1. Thus the series ues approaching 1 and −1. In particular,

therefore,
X cos2 (k) lim an 6= 0 .
n→∞
2k
k=1
Consequently, by the Divergence Test, the
converges if the series
∞ series is divergent .
X 1
2k
k=1
008 10.0 points
converges. But this last series is a geometric
series with Determine whether the series
1
r = < 1,
2 ∞
X n
hence convergent. Consequently, the given (−1)n
ln(n)
series is n=2

## is conditionally convergent, absolutely con-

absolutely convergent .
vergent, or divergent.
james (jaj4329) – HW 11.05 – rusin – (52435) 5
The given series can be rewritten as
1. series is conditionally convergent ∞ ∞
X 2 X
(−1)n = 2 (−1)n f (n) ,
n ln(n)
2. series is absolutely convergent n=2 n=2

where
3. series is divergent correct 1
f (x) = = (x ln(x))−1 > 0
x ln(x)
Explanation:
By the Divergence Test, a series for all x > 1. On the other hand, by the Chain
and Product Rules,

X
(−1)n an 1
f ′ (x) = − (ln(x) + 1) < 0
n=N (x ln(x))2
will be divergent for each fixed choice of N if for all x > 1. Thus f (x) is positive and
decreasing for all x > 1. But the improper
lim an 6= 0 integral
n→∞
Z ∞ Z ∞
1
since it is only the behaviour of an as n → ∞ f (x) dx = dx
that’s important. Now, for the given series, 2 2 x ln(x)
N = 2 and does not converge. By the Integral Test,
n
an = . therefore, the given series is not absolutely
ln(n)
convergent. It could still converge condition-
But by L’Hospital’s Rule, ally, however. To use the Alternating Series
Test to show that the series
x 1
lim = lim = ∞. ∞
x→∞ ln(x) x → ∞ 1/x X
(−1)n f (n)
Consequently, by the Divergence Test, the n=2
given series is is convergent, we have to check that
divergent . (i) f (n) > f (n + 1) for n ≥ 2,
(ii) lim f (x) = 0 .
x→∞
009 10.0 points
Since f is decreasing for all x ≥ 2, however,
Determine whether the series we see that

X 2 n ≥ 2 =⇒ f (n) > f (n + 1) .
(−1)n
n ln(n)
n=2 On the other hand,
converges conditionally, converges absolutely, 1
lim = 0.
or diverges. x→∞ x ln(x)

## 1. series converges conditionally correct Consequently, by the Alternating series Test,

the given series is
2. series diverges
conditionally convergent .
3. series converges absolutely
Explanation: 010 10.0 points
james (jaj4329) – HW 11.05 – rusin – (52435) 6
Determine whether the series for all x > 0, while

X 1 lim f (x) = 0 .
(−1)k−1 √ x→∞
k=1
1 + k2
But ak = f (k). Consequently,
is absolutely convergent, conditionally con-
vergent, or divergent. ak+1 < ak , lim ak = 0 .
k→∞

## 1. conditionally convergent correct By the Alternating series test, therefore, the

series

2. absolutely convergent X
(−1)k−1 ak
k=1
3. divergent
converges, and so the given series is
Explanation:
The given series has the form of an alter-
nating series conditionally convergent .

X 1
(−1)k−1 ak , ak = √ .
k=1
1 + k2

## To check for absolute convergence we apply

the Limit Comparison Test with
1 1
ak = √ , bk = .
1 + k2 k
For then
ak k
lim = lim √ = 1 > 0.
k → ∞ bk k→∞ 1 + k2
X
Thus the series ak converges if and only
if the series

X 1
k
k=1
converges. But, by the p-series test with
p = 1, this last series diverges; in particular,
the given series does not converge absolutely.

## To check if the given series converges con-

ditionally, consider first the function
1
f (x) = √ .
1 + x2
Then, by the Chain Rule,
x
f ′ (x) = − < 0
(1 + x2 )3/2